Human resource planning strategy to improve employee performance in facing the industrial revolution 4.0 - Prabowo, Satria Agung; Prasetiyo, Arditiya Bayu; Prasetya, Arief Budi; Supratikta, Hadi (ProBisnis : Jurnal Manajemen, 2023)
This study was prompted by a change in business policy that substituted human labor with machine labor, as a result of increasingly advanced technology breakthroughs. One option is to develop a Human Resources planning strategy for the period of Industrial Revolution 4.0, so that employees are not defeated by machines in the future. The problem formulation in this study is, "What is the Human Resources planning strategy in the Industrial Era 4.0?" The purpose of this study is to examine Human Resources planning methodologies in the Industrial Revolution 4.0. This research approach is literature, in which data is gathered through the use of references such as books, scientific journals, newspapers, periodicals, and documents. According to the findings of this study, HR planning tactics for improving employee performance include recruitment, career planning, and evaluation. The study's conclusion is that in order to improve employee performance, firms must understand their employees' personalities and place them in jobs that match their areas of expertise.